Gut microbiome profiling of neonates using Nanopore MinION and Illumina MiSeq sequencing - Cha, Teahyen; Kim, Hoo Hugo; Keum, Jihyun; Kwak, Min-Jin; Park, Jae Yong; Hoh, Jeong Kyu; Kim, Chang-Ryul; Jeon, Byong-Hun; Park, Hyun-Kyung (Frontiers in Microbiology, 2023)
This study aimed to evaluate the difference in gut microbiomes between preterm and term infants using third-generation long-read sequencing (Oxford Nanopore Technologies, ONT) compared with an established gold standard, Illumina (second-generation short-read sequencing). A total of 69 fecal samples from 51 term (T) and preterm (P) infants were collected at 7 and 28 days of life. Gut colonization profiling was performed by 16S rRNA gene sequencing using ONT. We used Illumina to validate and compare the patterns in 13 neonates. Using bioinformatic analysis, we identified features that differed between P and T. Both T1 and P1 microbiomes were dominated by Firmicutes (Staphylococcus and Enterococcus), whereas sequentially showed dominant transitions to Lactobacillus (P < 0.001) and Streptococcus in T2 (P = 0.001), and pathogenic bacteria (Klebsiella) in P2 (P = 0.001). The abundance of beneficial bacteria (Bifidobacterium and Lactobacillus) increased in T2 (P = 0.026 and p < 0.001, respectively). These assignments were correlated with the abundance at the species-level. Bacterial α-diversity increased in T (P = 0.005) but not in P (P = 0.156), and P2 showed distinct β-diversity clustering than T2 (P = 0.001). The ONT reliably identified pathogenic bacteria at the genus level, and taxonomic profiles were comparable to those identified by Illumina at the genus level. This study shows that ONT and Illumina are highly correlated. P and T had different microbiome profiles, and the α- and β-diversity varied. ONT sequencing has potential for pathogen detection in neonates in clinical settings.